Advanced Nanoindentation in Materials - Matt Pharr (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This Special Issue "Advanced Nanoindentation in Materials" contains some of the latest developments in the field of small-scale contact mechanics for a wide range of materials and biological cells. The featured manuscript revealed a new ultra-high strain rate nanoindentation method that will enable new scientific understanding of time-dependent material properties. The book also presents unique material properties of super alloys and other structural materials characterized by indentation methods. In addition to engineering materials, deformation behaviors of live cancer cells on sharp pillar structures were discussed in this book with the hope to stimulate interest in the mechanical contact behaviors of biological cells.